2021
DOI: 10.1111/irv.12913
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS‐CoV‐2 during a 2‐h domestic flight to Okinawa, Japan, March 2020

Abstract: Background Coronavirus disease (COVID‐19), caused by severe acute respiratory syndrome coronavirus (SARS‐CoV‐2), has rapidly spread globally. Potentially infected individuals travel on commercial aircraft. Thus, this study aimed to investigate and test the association between the use of face masks, physical distance, and COVID‐19 among passengers and flight attendants exposed to a COVID‐19 passenger in a domestic flight. Methods This observational study investigated pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…These equations funded on the well mixed room hypothesis are the basis of the famous Wells-Riley model and are convenient for a very large number of indoor situations. However, inhomogeneous infection patterns are reported for a number of well-documented transmission events in closed spaces, especially in restaurants [14-16] but also in other places such as aircrafts [17]. Generally, in these specific well studied cases, inhomogeneity was created by the mechanical ventilation system of air conditioning (hereafter AC) with recirculation, inducing locally larger air velocity.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…These equations funded on the well mixed room hypothesis are the basis of the famous Wells-Riley model and are convenient for a very large number of indoor situations. However, inhomogeneous infection patterns are reported for a number of well-documented transmission events in closed spaces, especially in restaurants [14-16] but also in other places such as aircrafts [17]. Generally, in these specific well studied cases, inhomogeneity was created by the mechanical ventilation system of air conditioning (hereafter AC) with recirculation, inducing locally larger air velocity.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Table 6 lists the 22 studies on COVID-19 transmission and/or prevalence on airplanes. Among them, 13 studies reported in-flight transmission rates ranging from 0% to 10% with a median of 0.36% [ 7 , 12 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] ]. The highest transmission rate of 10% was reported on a domestic flight in Japan where 14 passengers were infected [ 87 ].…”
Section: Sars-cov-2 Transmission In Public Transportmentioning
confidence: 99%
“…They concluded that there was potential COVID‐19 transmission in airplane cabins. Toyokawa et al 5 studied passengers and flight attendants exposed to COVID‐19 during a flight on March 23, 2020. By using whole‐genome sequencing of SARS‐CoV‐2 to identify the infectious linkage, they found a secondary attack rate of 9.7%.…”
Section: State‐of‐the‐art In Cabin Air Environment Designmentioning
confidence: 99%
“…A study by Boeing 3 showed that the global risk of COVID‐19 transmission during air travel was 1 in 1.7 million. However, other studies have reported an attack rate of 9.7% to 62% 4,5 . The flying public has reasonable doubts about the ability of modern airliners to protect them from infection by airborne diseases such as COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation